Dialogic Cosmopolitanism and Global Justice - JORDAAN, Eduard (Institutional Knowledge at Singapore Management University, 2009)
Although the term “cosmopolitan-communitarian debate” never really caught on, a national-global fault line remains prominent in debates about global justice. “Dialogic cosmopolitanism” holds the promise of bridging this alleged fault line by accepting many of the communitarian criticisms against cosmopolitanism and following what can be described as a communitarian path to cosmopolitanism. This article identifies and describes four key elements that distinguish dialogic cosmopolitanism: a respect for difference; a commitment to genuine dialogue; an open, hesitant and self-problematising attitude on the part of the moral subject; and an undertaking to expand the boundaries of moral concern to the point of universal inclusion. While offering much that is attractive, the dialogic cosmopolitan approach ultimately stumbles by failing to include large swathes of the global poor into the transnational moral community it aims to construct and by paying inadequate attention to matters of distributive justice.